USING SITUATIONAL APPROACH IN TEACHING ENGLISH AT SMP NEGERI 1 SIAU TIMUR - Salindeho, Florensia; Ronny Tuna, Jim; Liando, Nihta (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The application of a situational approach in English and its impact on student accomplishment are the main subjects of this study. The aim of this study is to determine whether the academic performance of students who get English instruction through a situational approach differs significantly from that of students who do not receive such instruction. In this study, 58 seventh-grade students from SMP Negeri 1 Siau Timur served as samples. This research uses a quantitative research design which is an experimental research. Data collection was carried out through tests to obtain information about student achievement in English. The test consists of 3 parts with a total of 25 questions. The T-test formula was utilized for data analysis. To ascertain whether the observed T value is significant in relation to the critical value of t, the value was 5.79. The authors utilize a miscellaneous table with level of significance = 0.025 to examine the critical t. Degrees of freedom (df) = 56 is the outcome. At a significance level of 0.025, the critical value of t for 56 is 2.004. 5.79 is the observed value of t. Use the H0 criteria to examine whether the null hypothesis is accepted or rejected. If t observed is less than or equal to t critical, then H0 is accepted; otherwise, it is rejected. In this case, since t observed 5.79 ≥ t critical 2.004, Hence, the null hypothesis is disproved. Since there is a statistically significant difference between the experimental group’s and the control group’s scores among seventh-grade students at SMP N 1 Siau Timur, the writer’s alternative hypothesis is supported.